Menstruation Awareness, Beliefs and Taboos: A Study of Gujarat (India) - Smruti Bulsari; Minasree Saikia; Gaurang Rami; Kiran Pandya (Philippine Association of Institutions for Research, Inc., 2021)
Menstruation is an integral yet neglected aspect of a woman's health. The reasons for this neglect could be because of the beliefs and taboos associated with it. This study examines the awareness and beliefs about menstruation and taboos practiced during the menstrual cycles. This study focuses on girls and women from different socioeconomic backgrounds in Gujarat, India. The data are collected by administering a questionnaire. Simple linear regression is undertaken to examine the influence of socioeconomic factors on awareness, beliefs, and taboos. The results reveal that education, region (rural and urban), and the extent of development of the district (developed, developing, tribal) are the main factors that influence the awareness, beliefs, and taboos associated with menstruation. However, occupation influences awareness, marital status, and family type influence beliefs, whereas age and religion influence taboos.